Assessing Teach-Back Utilization in a Downtown Medical Center - Karen Komondor; Ryan Choudhury (SLACK Incorporated, 2021)
Background: The St. Vincent Charity Medical Center's Patient and Family Education Policy directs staff to provide patients with easy-to-understand written and verbal communication. This includes using plain language and Teach-Back. Teach-Back-or asking patients to explain in their own words what they have learned-is a best practice that health care professionals use to ensure patient understanding. The effective use of plain language is key to using Teach-Back successfully. From random audits, we could assess whether staff were documenting their use of Teach-Back. We had not, however, ascertained whether that documentation was a true account of the use of Teach-Back. Brief description of activity: We created a three-part project to (1) assess staff knowledge and use of Teach-Back, (2) assess and address barriers to use of Teach-Back, and 3) assess patients' recall of their providers using Teach-Back. Implementation: Internal medicine resident physicians (hereafter termed "residents") and nurses completed an anonymous, online survey regarding their experience with Teach-Back. After vetting, these responses were integrated into mandatory provider training. Focusing on health literacy and Teach-Back, the training addressed barriers, reinforced positive experiences, and tailored practice encounters to patients. We then randomly surveyed inpatients to assess their recall of their providers using Teach-Back. Results: The majority (96.3%) of providers indicated that Teach-Back should be used frequently. Only 79.9%, however, reported using Teach-Back. Providers regarded Teach-Back as important and rated their confidence level as high. Providers also reported barriers to Teach-Back. Of the 135 patients surveyed, 46% recalled their providers using this method. Lessons learned: We note a gap between providers' self-reported use of Teach-Back and patients' recall of their providers using it. Providers may be overstating their utilization rate. The survey, further, assessed patients at random points in their hospital stays, to include those who had not yet received Teach-Back education. These factors could contribute to the observed discrepancy. Most notably, results confirmed our position that regular provider training helps address barriers and misconceptions about Teach-Back. [HLRP: Health Literacy Research and Practice. 2021;5(3):e226-e232.] Plain Language Summary: Our Health Literacy Institute was created in 2007 after receiving a grant to institutionalize health literacy across the continuum of patient care. Health literacy refers to a person's ability to obtain, understand, and process basic information, which empowers them to make appropriate health decisions.